Araab (Villagers) In The Blessed Life Of The Prophet - Dr Hafiz Muhammad Ibrar Ullah , Dr. Nighat Akram , Dr. Fareed-Ud-Din Tariq , Dr. Farida Begum , Dr. Muhammad Riaz , Dr. Bashir Ahmad Malik (Migration Letters, 2024)
The Araab are rural people, even if they are non-Arabs. These inhabitants were often Arabs who wandered about in search of water and grass and did not live in towns and cities and did not enter them unless necessary. They were simple people, their l[1]ife was also simple, they mostly did farming and raising goats. A study shows that the blessed period of the Companions ended at the end of the first century. In villages, deserts, and cities, human nature is the same everywhere. There are disbelievers and believers among the villagers and desert dwellers. But their disbelief and their hypocrisy are very Hard and intense compared to others. Ignorance creates intensity, so the person who is used to intensity for no reason is away from knowledge. The hypocrites who live in the villages are more strict in disbelief and hypocrisy than those who live in the city, the reason for this is that they stay away from the gatherings of knowledge and the company of scholars, and they do not listen to the Quran and Hadith and sermons and advice. Just as God is one, His truth is also the same and it has never been the inheritance of a particular nation, a particular community, and a particular group.